Role of calcium-sensing receptor in regulating activation susceptibility of postovulatory aging mouse oocytes - Rui YANG; Chang-Li JI; Min ZHANG; Jie ZHANG; Hong-Jie YUAN; Ming-Jiu LUO; Guang-Zhong JIAO; Jing-He TAN (The Journal of Reproduction and Development, 2023)
The mechanisms underlying postovulatory oocyte aging (POA) remain largely unknown. The expression of the calcium-sensing receptor (CaSR) in mouse oocytes and its role in POA need to be explored. Our objective was to observe CaSR expression and its role in the susceptibility to activating stimuli (STAS) in POA mouse oocytes. The results showed that, although none of the newly ovulated oocytes were activated, 40% and 94% of the oocytes recovered 19 and 25 h after human chorionic gonadotropin (hCG) injection were activated, respectively, after ethanol treatment. The level of the CaSR functional dimer protein in oocytes increased significantly from 13 to 25 h post hCG. Thus, the CaSR functional dimer level was positively correlated with the STAS of POA oocytes. Aging in vitro with a CaSR antagonist suppressed the elevation of STAS, and cytoplasmic calcium in oocytes recovered 19 h post hCG, whereas aging with a CaSR agonist increased STAS, and cytoplasmic calcium of oocytes recovered 13 h post hCG. Furthermore, the CaSR was more important than the Na-Ca2+ exchanger in regulating oocyte STAS, and T- and L-type calcium channels were inactive in aging oocytes. We conclude that the CaSR is involved in regulating STAS in POA mouse oocytes, and that it is more important than the other calcium channels tested in this connection.